World Heritage Convention and Transnational Legal Process to Protect Indonesian Nature - Ary Aprianto (Faculty of Law, Universitas Padjadjaran, 2019)
The World Heritage Convention demands its states parties to strengthen mechanisms to conserve and preserve natural and cultural heritage consistently. A party to the Convention, Indonesia faces challenges to maintain the balance of economic, social, and environment considerations, pertaining to policies that affect natural heritage. Nevertheless, Indonesia remains committed to observe the Convention’s rules, including ones on sustainability and conservation. As analyzed through transnational legal process theory, the performance of this commitment helps to internalize the Convention’s rules into domestic context. It is suggested that Indonesia step up its interaction with the Convention’s actors in the hope of expanding the internalization of the Convention since it will help Indonesia to design better nature conservation and preservation mechanism.Konvensi Warisan Dunia dan Transnational Legal Process untuk Melindungi Alam IndonesiaAbstrak Konvensi Warisan Dunia menuntut negara-negara pihak konsisten memperkuat mekanisme konservasi dan pelindungan warisan alam dan budaya. Walaupun telah menjadi negara pihak, dalam membuat kebijakan yang berdampak pada warisan alam, Indonesia tetap menghadapi tantangan dalam menjaga keseimbangan antara pertimbangan ekonomi, sosial, dan lingkungan. Namun demikian, Indonesia tetap berkomitmen melaksanakan ketentuan konvensi, termasuk mengenai kelestarian dan konservasi. Setelah dianalisis menggunakan teori transnational legal process, pelaksanaan komitmen ini membantu proses internalisasi ketentuan-ketentuan konvensi ke tataran nasional. Disarankan agar Indonesia meningkatkan interaksi dengan para aktor konvensi guna mendorong proses internalisasi lebih lanjut, karena internalisasi ini membantu Indonesia membuat mekanisme konservasi dan preservasi alam yang lebih baik. Kata kunci: Konservasi Alam, Konvensi Warisan Dunia, Transnational Legal Process.DOI: https://doi.org/10.22304/pjih.v6n3.a4